Enhanced antitumor activity in A431 cells via encapsulation of 20(R)-ginsenoside Rg3 in PLGA nanoparticles. (3rd October 2017) - Zhang, Shaozhi; Liu, Jiwei; Ge, Baojian; Du, Meiling; Fu, Li; Fu, Yushan; Yan, Qiu
Abstract: Objective: The objective of this study is to investigate the encapsulation of 20(R)-ginsenoside Rg3 (20(R)-Rg3) using polylactic-co-glycolic acid (PLGA) and promotion for its antitumor activity. Significance: Preparation and evaluation of the antitumor efficacy of 20(R)-Rg3-loaded PLGA nanoparticles were the first reported. The data will be helpful to apply 20(R)-Rg3 efficiently and broadly in new drug form development and clinical cancer treatment. Methods: The nanoparticles were prepared using emulsion and solvent evaporation methods. The uniform particle size and good dispersion were further confirmed by scanning electron microscopy. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was applied to detect cell proliferation after 20(R)-Rg3-loaded PLGA nanoparticles treatment. Western blotting and immunofluorescent staining were used for observation of key proteins related with proliferation and apoptosis. Cell cycle and apoptosis were analyzed by flow cytometer technology. Results and discussion: The results showed that the size of 20(R)-Rg3-loaded PLGA was 97.5 nm in diameter, and zeta potential was −28 mV detected by Malvern particle size analyzer. The encapsulation efficiency was 97.5%, and drug loading was 70.2% measured by high-performance liquid chromatography. The in vitro study showed that the encapsulated 20(R)-Rg3 was consecutively released and the release ratio reached to the highest value (19.36%) at the time point of 96 h. The encapsulated 20(R)-Rg3 significantly inhibited the proliferation and induced apoptosis in A431 cancer cells compared with the unencapsulated 20(R)-Rg3, control and PLGA alone. Conclusion: 20(R)-Rg3-loaded PLGA nanoparticles was well prepared and characterized. The antitumor activity was increased after PLGA encapsulation. The data will be beneficial to the development of new dosage forms of 20(R)-Rg3 and extensive application.